JAVA FOR DEVELOPERS POCKET PRIMER - CAMPESATO, OSWALD (MERCURY LEARNING & INFORM, 2022)
As part of the best-selling Pocket Primer series, this book is designed to provide a thorough introduction to Java development for people who are relatively new to the Java programming language. It is intended to be a fast-paced introduction to the core concepts of Java and Java APIs, illustrated with code samples using primarily Java 8. Companion files with source code are available. FEATURES:Covers Boolean logic, loops, arrays, recursion, OOP concepts, data structures, streams, SQL, and moreLists new features in Java 9 through Java 13Features numerous code samples throughoutIncludes companion files with source code.
Keywords: Software architecture.; Application software -- Development.; JavaScript (Computer program language); elektronické knihy; electronic books